Sistem Ekonomi dan Administrasi Islam - Rachmidha Sosfendri, Aqsha Elvinancy; Lestari, Dea; Syukri Azhari, Devi (UNIVERSITAS SERAMBI MEKKAH, 2025)
Civil society is a social concept that reflects a democratic, civilized life that upholds human values. In the context of Indonesia, civil society plays a crucial role in maintaining interfaith harmony amidst diversity. This study aims to analyze the role of civil society in strengthening social harmony and identifying the supporting and inhibiting factors in achieving interfaith harmony. Using a qualitative approach and literature study method, this research finds that civil society contributes to creating spaces for dialogue, increasing awareness of pluralism, and building inclusive social networks. However, challenges such as intolerance and social polarization remain obstacles to achieving sustainable harmony. Therefore, synergy between the government, community organizations, and individuals is necessary to strengthen the values of togetherness and tolerance.